# math... precalculus

posted by .

how do i solve this equation?
log3x+log3(x-24)=4

• math... precalculus -

I will assume you mean log3 for all

log3x+log3(x-24)=4

log3 (x/(x-24)) = 4
3^4 = x/(x-24)
81 = x/(x-24)
81x - 1944 = x
x = 24.3

## Respond to this Question

 First Name School Subject Your Answer

## Similar Questions

1. ### Math

(I have two questions) 1. Solve for x without a calculator: log3(x^2)=2log3(4)-4log3(5) This is what I have so far: 2log3(x)=log3(4^2)-log3(5^4) 2log3(x)=log3(16/625) ...and now I'm stuck. 2. Simplify: 2log4(9)-2log3 <--how do you …
2. ### Precalculus

Please help me with these questions ASAP!! Suppose that f(x)=log3(x-1) a)If f(6)=1.4 and f(8)=1.7,then evaluate log3(35) and log3(7/5). b)If f(3)=0.6, find log9(2).
3. ### Pre-Cal

1) Solve the equation exactly for x: log3 x - log3(x-3) = 2 I got 1 as an answer. Is this correct?
4. ### math (pre-calc)

Solve for x: 1. 3^2x+3^x+1-4=0 2. log3(x=12)+log3(x+4)=2 3. lnx+ln(x+2)=4 4. 3*4^x+4*2^x+8=0
5. ### Math

Solve for x. log3(x+7)=2-log3(x-1) Write the exact answer using base-10 logarithms.
6. ### Algebra

Solve the equation. 2log3 y = log3 4+ log3 (y+8) Here's what ive got take out the logs and say y^2= 4+ y +8 which simplifies to (y^2)-y=12 how do i simplfy the y?
7. ### Math

Solve the logarithmic equation. Express your solutions in exact form only. Please show all of your work. log3(x+2) + log3(x+8) – 2 = log3(x+3)
8. ### math

Solve for x in the following equations. (4 marks) log3(x - 5) + log3(x + 3) = 2 <--- both log3.. 3 is subscript log7x + log7(x - 1) = log72x <--- all log7.. 7 is subscript.
9. ### Algebra (logs)

Please help, I need help on these two problems. Solve the equation. log3(x − 16) = log3(9x) e^1 + ln(7) It appears on the homework that the ln(7) is written like this ^ln(7) but I am still stuck on it. Thanks!
10. ### MATH Precalculus

Use the Laws of logarithms to rewrite the expression log3(x^18*sqrt3(y12)) in a form with no logarithm of a product, quotient or power. After rewriting we have log3(x^18*sqrt3(y12))=Alog3(x)+Blog3(y) With the constant A=?

More Similar Questions